Quantifying the Influence of Larval Density on Disease Transmission Indices in Culex quinquefasciatus, the Major African Vector of Filariasis. (June 2019) - Ukubuiwe, Azubuike Christian; Ojianwuna, Chioma Cynthia; Olayemi, Israel Kayode; Arimoro, Francis Ofurum; Omalu, Innocent Chukwuemeka James; Ukubuiwe, Chinenye Catherine; Baba, Bulus Musa
Larval crowding is one of the abiotic factors affecting biological fitness in mosquitoes. This study aims at elucidating, quantitatively, the influence of more larval crowding on aspects of fitness in Culex quinquefasciatus mosquito. To this end, day-old larvae of the species were reared in 4 density regimens equivalent to 1 larva in 1.25, 2.5, 5, and 10 mL of distilled water. Developmental indices, adult fitness indices, and accumulation and utilisation of teneral reserves for metamorphosis were determined at these density regimens. The results revealed varying significant negative effects of larval density on all fitness indices measured for the species. The study also revealed high utilisation of teneral reserves for metamorphosis at high larval densities. The information generated will be useful in making informed-decisions in allocating scare resources for vector control, although field trials are advocated to establish these laboratory findings.